Comparative analysis of physical fitness and motor coordination abilities of students of the first and second courses of higher educational institutions engaged in aerobics - Fomenko, O.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to analyze the method of applying modern health technologies, taking into account varying degrees of motivation and physical condition of students. Material: 358 students aged 16-19 years took part in the experiment. The analysis of more than 50 references, studies devoted to the peculiarities of the female body health forming technologies. Results: significant increase of interest in physical education classes using the suggested health forming technologies. Established that the main ways to improve physical education students can be formed needs in health promotion by means of aerobics, shaping, Pilates, Callanetics. Conclusions: The identified prospect of improvement of physical education students, which allows the structured problems they need to develop options and solutions to the successful implementation of health- education strategy.